Analysis of Critical Moisture and Water Activity of Malaysian Sata and Its Implication to Product Characteristics and Shelf Life - Rita Hayati; Aminah Abdullah; Mohd Khan Ayob; Soewarno T Soekarto (Jurnal Teknologi dan Industri Pangan, 2005)
Critical moisture and water activity of Sata. a Malaysian traditional food made of fish and young coconut meats, were analyzed for the first and second critical points of transition among the primary, secondary and tertiary bound water fractions in the Sata. It was found out that the first critical points of moisture content and water activity were M, of 5.09 % db (4.73 % wb) and ar of 0.44 respectively. The second critical points were water content M5 of 19.38 % db(15.2 % wb) and water activity as of 79 % respectively. The upper limit of he tertiary bound water (Mt) was 75.3 % db (43.0 % wb). Sate sample in the primary bound water fraction (represented by moisture content at 5.0 % rib / 4.73 % wb), was stable in color and appearance, but slightly rancid due to molecular mobility of the liquid oil content The sample in the secondary bound water fraction (represented by moisture content of 15.0% db / 13.0% wb), has a color change to darker brown: and in the tertiary bound water fraction (represented by moisture of 30.5 % db / 23.4 % wb), mold growth appeared on the 10th day storage. The characteristics of the Malaysian Sate indicated an intermediate moisture food (IMF) with water content of 37.5% wb, water activity of 0.9 and limited shelf tile to, few days at room temperature. Key words : Malaysian sata critical aw. critical moisture, sorption isotherm, shelf life